Glucuronidation and the UDP - glucuronosyltransferases - Mackenzie, Peter; Miners, John (Henry Stewart Talks, 2007)
The glucuronidation reaction, UGT enzyme superfamily, Importance for xenobiotic and drug metabolism, Substrate and inhibitor specificities, Gene regulation, Tissue specific expression, Genetic polymorphism, Structure/function relationships, Kinetic considerations
Archived at 2016/02/09